2020
DOI: 10.3390/plants9121791
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Resources to Cyanogenic Glucosides Does Not Incur a Growth Sacrifice in Sorghum bicolor (L.) Moench

Abstract: In plants, the production of secondary metabolites is considered to be at the expense of primary growth. Sorghum produces a cyanogenic glycoside (dhurrin) that is believed to act as its chemical defence. Studies have shown that acyanogenic plants are smaller in size compared to the wildtype. This study aimed to investigate whether the small plant size is due to delayed germination or due to the lack of dhurrin derived nitrogen. A novel plant system consisting of totally cyanide deficient class 1 (tcd1) and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Delayed growth was not observed in the acdc1 mutants that contain similar concentrations of dhurrin to the wildtype when young or in the sibling line which has the same background, but lacks the mutation. This reduced growth of tcd1 at the earliest stages of plant development is consistent with previous results investigating this particular genotype under differing nitrogen regimes (Blomstedt et al 2018 ; Sohail et al 2020 ). Our experiment did not look at whether these mutants were more vulnerable to herbivores.…”
Section: Discussionsupporting
confidence: 92%
“…Delayed growth was not observed in the acdc1 mutants that contain similar concentrations of dhurrin to the wildtype when young or in the sibling line which has the same background, but lacks the mutation. This reduced growth of tcd1 at the earliest stages of plant development is consistent with previous results investigating this particular genotype under differing nitrogen regimes (Blomstedt et al 2018 ; Sohail et al 2020 ). Our experiment did not look at whether these mutants were more vulnerable to herbivores.…”
Section: Discussionsupporting
confidence: 92%
“…This observation suggests that carbon and nitrogen pools otherwise committed to dhurrin biosynthesis may be redirected to support a higher growth rate of vegetative tissues. This differs from what was reported for the totally cyanide deficient mutant1 (tcd1), that exhibited delayed germination (Montini et al 2020), reduced growth during early seedling growth (Blomstedt et al 2012), and altered flowering times (Sohail et al 2020). The reduced growth during germination in tcd1 plants likely highlights importance of recycling dhurrin for germination and early seedling growth (Montini et al 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have consistently found young sorghum plants and immature tissues of older plants to have much higher concentrations of cyanogenic glucosides (Halkier and Møller 1989 ; Miller et al 2014 ; Blomstedt et al 2018 ; Sohail et al 2020 ; Cowan et al 2021 ). Here we determined that the HCNp in roots was highest in a region immediately adjacent to the root tip that spans the growing zone, with a significantly lower concentration in the older tissue of the maturation zone (Table 2 b; Fig.…”
Section: Discussionmentioning
confidence: 96%
“…While this approach is excellent at explaining why costs of defence change as plants mature (Boege and Marquis 2005 ), it does not account for the fact the costs are sometimes not detectable (e.g. (Sohail et al 2020 )). Results support the conjecture that dhurrin is not purely synthesised for defence but is integrated with the primary metabolism in sorghum functioning as a mobilizable source of reduced nitrogen during grain filling and germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation